Tarenna charlesii, a new species of Tarenna (Rubiaceae) from southern Western Ghats - Maya, Sukumaran Nair; Pillai, Sunilkumar Thrivikraman; Antony, Valiiyaveettil Thomas (Phytotaxa, 2024)
Tarenna charlesii (Rubiaceae), a new species from Palakkad district of Kerala, southern parts of Western Ghats is described. Detailed descriptions, distribution, key to the south Indian species are provided along with SEM comparison of the pollen.